Streptococcus agalactiae Septic Arthritis of the Shoulder and the Sacroiliac Joints: A Case Report - Yahia Z. Imam; Housam Aldeen Sarakbi; Nagui Abdelwahab; Issa Mattar (Case Reports in Rheumatology)
Invasive group beta-streptococcal arthritis is being increasingly diagnosed as suggested by recent data. We report a case of a middle-aged lady from Sri Lanka who developed septic arthritis of the right shoulder and the left sacroiliac joint as well as an iliopsoas collection caused by Streptococcus agalactiae shortly after labor at Hamad General Hospital in Doha, Qatar. We conclude that Streptococcus agalactiae septic arthritis is rare. It can present with invasive disease in adults. It usually targets older females and immuno compromised patients especially those with risk factors for bacteraemia. Therefore a high index of suspicion is needed. Shoulder and sacroiliac joint affection is not uncommon for unknown reasons. Utilizing imaging modalities such as ultrasonography and magnetic resonance imaging is helpful.